ISLAMISME: KEMUNCULAN DAN PERKEMBANGANNYA DI INDONESIA - Siti Mahmudah (IAIN Manado, 2018)
Abstract. This study examines the origin, existence, and development of Islamism group in Indonesia since pre-independence until now. Islamism is a group of Muslims who are obedient to the teachings of Islam, but they are very extreme, literal, static and rigid in understanding the teachings of Islam (Alquran), and reject to the other Muslims who disagree with Islamic ideology that they have embraced. The group of Islamism existed and emerged in Indonesia, it was not apart from the influence of the spread of Islamic teachings from al-Ikhwan al-Muslimun that was founded by Hasan al-Banna in Egypt in 1928. The group of Islamism was the first Muslim group before the other Muslim groups in Indonesia; such as the Pos-Islamism group, the Liberal Islam Group, the Moderate Islamic Group, the Progressive Islam Group. The group of Islamism in Indonesia—as al-Ikhwan al-Muslimun in Egypt who aspires to spread the ideology of Islam for all of the world—seeks to spread their ideology with the movement of